Analisis Laporan Keuangan Guna Keputusan Investasi:: Studi Kasus PT.Indofood Sukses Makmur Tbk. - Mutia Sari; Budi Dharma; Fakri Mursala (Economic Reviews Journal, 2023)
This study aims to determine the effect of the company's health or the value of the company on investment decisions obtained from the aspects of probability, liquidity, cash ratio, and leverage. invest the funds in this decision, in this case the case study company PT. Indofood Sukses Makmur, Tbk. The source of the data obtained is secondary data issued by the company in the form of a financial overview from 2017 to 2021 or the previous 5 years where the data obtained several conclusions regarding PT Indofood's company finances, namely experiencing many changes - good changes from probability, liquidity, cash ratio. and leverage in 2017 to 2021 but the influence and decrease in numbers is not that significant even though in 2019 many companies are experiencing difficulties due to the co-19 pandemic. The method used in this study is a descriptive qualitative method of secondary data obtained to be managed from a predetermined formula according to Charles H Gibson in his book Financial Reporting analysis using financial accounting information. The results obtained in this study are that PT Indofood has experienced consistency in managing its finances from the past 5 years and the possibility of a greater return on shares and no losses so that investors can place their funds in Indofood companies. Keywords: Financial Report Analysis, Investment